(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In this work, the methods of implementation of the SM4 encryption algorithm transformations in the Python programming language were studied. It was found that the implementation of S-box in the form of a 1-dimensional table allows to achieve efficiency in terms of time. An efficient method has also been found for the cyclic left shift operation. The results obtained for the code written in the Python programming language for the encryption algorithm were compared with other implementation options in terms of the time spent on encryption and decryption, and it was found that this implementation method allows to achieve higher efficiency in terms of time.